ANALISIS ALTMAN Z-SCORE UNTUK MEMPREDIKSI KEBANGKRUTAN - Nofitasari, Heni; Nurulrahmatia, Nafisah (Balance : Jurnal Akuntansi dan Bisnis, 2021)
This study aims to predict bankruptcy in pharmaceutical companies listed on the IDX for the 2015-2019 period using the Altman Z-Score method. The research method used in this research is descriptive research with a quantitative approach. The population in this study were all manufacturing companies in the pharmaceutical sub-sector consumer goods industry which consisted of 9 companies listed on the IDX from 2015 to 2019 with a sample of 4 companies. The sampling technique used was purposive sampling. The research instrument used in this research is financial statements. The data collection technique used was literature study and the data analysis technique used was the one-sample t-test. The results of this study prove that by using the Altman Z-Score analysis method, it is known that pharmaceutical companies listed on the IDX for the 2015-2019 period are predicted not to have the potential to experience bankruptcy because the average Z value ? 1.81. this means that pharmaceutical companies are in a prone condition of bankruptcy to health.